Putting strategic partnership to the test: Cooperation between NATO and the EU in Operation Althea - Frank Kupferschmidt (Stiftung Wissenschaft und Politik (SWP), 2006)
Operation Althea in Bosnia-Herzegovina has been the most demanding military operation led by the EU. It represents the high point of NATO-EU cooperation in crisis management to date.However, relations between NATO and the EU only partly live up to the agreed principles of "strategic partnership" - this is one finding of an analysis of the two organisations' cooperation in the preparatory phase of Althea and the first year of the operation. The greatest deficits exist between the political committees of NATO and the EU. Since all decisions require consensus in both organisations, and the number of members has increased, it is here that problems are most likely to occur. Different ideas and divergent interests delayed decisions in the lead-up to Operation Althea. At military level the agreements between NATO and the EU have been utilised effectively and professionally. But Althea has also showed up limitations: the complexity of the arrangements and the long preparation time mean that their application will be limited to NATO-successor operations. General progress has been made in recent years in crisis-management cooperation between NATO and the EU, but measures should now be taken to help consolidate this development - strategic dialogue should be intensified, and when crises are looming the two organisations should meet at an early stage to discuss the situation, common goals and possible measures. (SWP-Research Papers / SWP)
Keywords: 320